Professional Preparation of Social Work Students in Light of Labor Market Requirements in Libyan Society (Comprehensive Journal of Science, 2026)
The study addresses the professional preparation of social work students in light of labor market requirements in Libyan society, analyzing the alignment between academic programs, practical training, and community needs. The research aims to highlight the role of professional preparation in equipping students with the knowledge and skills necessary for effective practice, linking theoretical learning with practical application to ensure successful integration into various work environments. The study employs a descriptive-analytical approach, examining educational programs, field training curricula, and relevant literature. Findings indicate that professional preparation enhances students’ competencies and their ability to meet professional challenges; however, a gap remains between theoretical knowledge and labor market needs. The study recommends improving curricula, developing field training, enhancing academic supervision, and strengthening university–labor market collaboration to produce well-qualified graduates.
Keywords: Professional preparation – Social work – Labor market – Students – Libyan society